2010
DOI: 10.4314/ijmu.v5i1.49293
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between anti-hypertensive and non-steroidal anti inflammatory drugs: implications in management of osteoarthritis and opinion on a compromise therapy

Abstract: The premise for this article is that a significant proportion of patients presenting in the clinic with osteoarthritis have hypertension as co-morbidity. A common drug of choice in managing symptoms of osteoarthritis including those affecting the knee joint is the Non-Steroidal Anti-Inflammatory Drugs (NSAIDS) groups. It has been reported however that NSAIDs diminish the effects of anti-hypertensive drugs and may lead to an ineffective hypertension therapy. In order to avoid complications in the health of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Determinants of eosinophil count among frequent NSAIDs users.The mean age of the NSAIDs users was less than what other studies found in Nigeria, Iran and in the United States[3] [5] …”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Determinants of eosinophil count among frequent NSAIDs users.The mean age of the NSAIDs users was less than what other studies found in Nigeria, Iran and in the United States[3] [5] …”
mentioning
confidence: 57%
“…NSAIDs use is very common in low-income nations like Nigeria, where there are significantly larger population of manual laborers and artisans due to the very low level of industrial mechanization compared to the developed countries [2]. NSAIDs use in treating rheumatic conditions is quite common in the elderly [3].…”
Section: Introductionmentioning
confidence: 99%
“…The higher prevalence of NSAIDs use in this study compared with the 13% found in a community study in Nigeria and the 14% reported in the United States, could be attributed to the study's (hospital-based) design and participants' NSAIDs-requiring conditions [2,6]. Another study in Nigeria also attributed NSAIDs use to the treatment of painful conditions and found a prevalence of NSAIDs use among males and females aged over 65 years to be 60% and 70% respectively, in a population that included diabetics and hypertensives, (groups that were both excluded from our study) [8]. Though the authors, did not assess kidney function in their study, they reported a poor response to antihypertensives among hypertensives who used the two drug groups concurrently.…”
Section: Discussionmentioning
confidence: 73%
“…In Nigeria, a prevalence of 60% and 70% NSAIDs use is reported among males and females aged over sixty five years respectively. The authors attributed the high prevalence to arthritis and other musculoskeletal conditions that are common in this population [8]. Renal complications from the use of these drugs is reported to cause about 2% of users to discontinue the drugs [9].…”
Section: Introductionmentioning
confidence: 99%